The Worlds of Carol Shields - Atwood, Margaret, 1939-; Staines, David, 1946- (Book collections on Project MUSE., 2014)
The Worlds of Carol Shields is the first book to examine Shields' extraordinary career and life through the lens both of close friends and of literary critics.